Mau'izah for teens in the novel Satu Bulan Tiga Bintang by Ummu Hani Abu Hassan - Kamarudin, Kamariah (Dewan Bahasa dan Pustaka, 2017)
There are several efforts being undertaken, to shape the personality of teens or young adults, based on Islamic perspective. One such effort is contained in the concept of mau’izah which includes advising and reminding one another towards virtue, truth and patience. The concept of mau’izah as portrayed in Islam is the core of education, particularly in shaping the personality of young adults towards embracing good values. It has been found that mau’izah is not only useful for uplifting the spirit of these young people, but it also provides good reading material for society at large. In line with this, literary works, especially teen novels are reading material that have the ability to shape the behaviour and personality of youths. Therefore, this study will explore mau’izah for teens in the novel Satu Bulan Tiga Bintang by Ummu Hani Abu Hassan to show the extent to which advising and reminding towards virtue is presented by the writer to the readers. This study clearly shows that the concept of mau’izah is utilized by the author with the intention of developing an excellent youth personality guided by Islamic principles in the midst of present-day modernization and technology. The effort to advise and remind others towards virtue, truth and patience has made the concept of mau’izah the main prerequisite for the development of humanity and nurturing of a human being.